Macroprudential and monetary policy rules: a welfare analysis - Rubio, Margarita; Carrasco-Gallego, José A. (Wiley, 2015)
This paper studies the interaction between macroprudential and monetary policies, using a DSGE model with a housing market and collateral constraints. Monetary policy follows a standard Taylor rule for the interest rate. The macroprudential authority implements a Taylor-type rule for the loan-to-value, ratio reacting to output and house prices. Results show that introducing the macroprudential rule or extending the interest-rate rule to respond to house prices increases welfare, since it enhances financial stability. However, for the optimal policy mix, when both policies act together, monetary policy should ensure price stability while the macroprudential authority should safeguard financial stability.